Patient reported outcomes after navigated minimally invasive hybrid lumbar interbody fusion (nMIS-HLIF) using cortical bone trajectory screws. Issue 50 (16th December 2022) - Sitoci-Ficici, Kerim Hakan; Jiang, Hongzen; Esmael, Agrin; Ruess, Daniel; Reinshagen, Clemens; Brautferger, Uta; Schackert, Gabriele; Molcanyi, Marek; Pinzer, Thomas; Hudak, Radovan; Zivcak, Jozef; Rieger, Bernhard
Abstract : Prospective observational study. To evaluate patient-reported outcomes after navigation-guided minimally invasive hybrid lumbar interbody fusion (nMIS-HLIF) for decompression and fusion in degenerative spondylolisthesis (Meyerding grade I-II). Posterior lumbar interbody fusion (PLIF) and transforaminal lumbar interbody fusion (TLIF) are well-known standard procedures for lumbar spinal fusion. nMIS-HLIF is a navigation-guided combined percutaneous and open procedure that combines the advantages of PLIF and TLIF procedures for the preparation of a single-port endoscopic approach. 33 patients underwent nMIS-HLIF. Core outcome measure index (COMI), oswestry disability index (ODI), numeric rating scale (NRS) back, NRS leg, and short form health-36 (SF-36) were collected preoperatively and at follow-up of 6 weeks, 3 months, 6 months, and 1 year. The impact of body mass index (BMI) was also analyzed. Computed tomography reconstruction was used to assess realignment and verify fused facet joints and vertebral bodies at the 1-year follow-up. 28 (85%) completed the 1-year follow-up. The median BMI was 27.6 kg/m 2, age 69 yrs. The mean reduction in listhesis was 8.4% ( P < .01). BMI was negatively correlated with listhesis reduction ( P = .032). The improvements in the NRS back, NRS leg, ODI, and COMI scores were significant at all times ( P < .001— P < .01). The SF-36 parameters of bodily pain, physical functioning, physical component summary, role functioning/physical functioning, and social functioning improved ( P < .003). The complication rate was 15.2% (n = 5), with durotomy (n = 3) being the most frequent. To reduce the complication rate and allow transitioning to a fully endoscopic approach, expandable devices have been developed. The outcomes of nMIS-HLIF are comparable to the current standard open and minimally invasive techniques. A high BMI hinders this reduction. The nMIS-HLIF procedure is appropriate for learning minimally invasive dorsal lumbar stabilization. The presented modifications will enable single-port endoscopic lumbar stabilization in the future.